1971
DOI: 10.1590/s0071-12761971000100023
|View full text |Cite
|
Sign up to set email alerts
|

Marcha de absorção de nitrogênio, fósforo, potássio, cálcio e magnésio na cultura da mamoneira (Ricinus communis, L.), cultivar "Campinas"

Abstract: INTRODUÇÃOAs primeiras referências sobre a composição química da mamoneara, no Brasil, foram apresentadas por GRANATO (1918), citando que em média as porcentagens de nitrogênio, potasa e ácido fosfórico eram respectivamente 1,39%, 1,25% Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

1977
1977
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…only p and ca showed a behavior different from the other nutrients; there was practically no ca uptake 85 dae, whereas p was the only nutrient absorbed until the end of the crop cycle. Nakagawa & Neptune (1971) also reported an increased p accumulation by the castor bean cultivar campinas until the end of the cycle.…”
Section: Macronutrient Accumulationmentioning
confidence: 85%
See 2 more Smart Citations
“…only p and ca showed a behavior different from the other nutrients; there was practically no ca uptake 85 dae, whereas p was the only nutrient absorbed until the end of the crop cycle. Nakagawa & Neptune (1971) also reported an increased p accumulation by the castor bean cultivar campinas until the end of the cycle.…”
Section: Macronutrient Accumulationmentioning
confidence: 85%
“…in the 50s, based on literature data, canecchio Filho & Freire (1958) estimated that in a yield of 2.000 kg ha -1 dry fruit (seeds + husk) yield, castor bean exports 80, 7.9, 26.7, 8.6 and 6.0 kg ha -1 of N, p, K, ca and Mg, respectively. in a subsequent study, Nakagawa & Neptune (1971) found that the nutrient amounts absorbed by this oilseed crop throughout the crop cycle (133 days) were 156 kg ha -1 N, 5.3 kg ha -1 p, 172 kg ha -1 K, 13.8 kg ha -1 ca and 12.5 kg ha -1 Mg, demonstrating the high nutrient demand during the growth and development of this crop. However, aside from not taking the micronutrients into consideration, the said studies involved cultivars with a long growth cycle, medium height and non-uniform maturity, suited for manual harvest only.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Nas análises químicas de nutrientes, tabelados no Quadro 8, o nitrogênio variou significativamente entre alguns tratamentos, mas, pelos resultados, fica claro que as flutuações observadas independem das doses de fósforo acarreta uma tendência à diminuição nos teores de potássio, cálcio e magnésio, e até mesmo no teor do próprio fósforo. Comparando esses dados com os obtidos por NAKAGAWA & NEPTUNE (1971) CONCLUSÕES a) O fósforo incrementou significativamente a produção de frutos, em peso e número, por parcela, e o número de frutos, por cacho, e a produção de sementes, em gramas por cacho. b) A ação Uo fósforo foi maior no aumento do número de frutos e, dentro dos tipos de cachos, os primários foram os mais influenciados .…”
Section: Discussionunclassified
“…Fifty percent of zinc and 60% of Cu uptaken, on average, in out-of-season is exported with grains, but for the other micronutrients the proportion exported with grains is less than 40%. Key words: Ricinus communis, mineral nutrition, absorption curves, absorption rates, yield introdução A maioria das informações existentes na literatura sobre absorção e exportação de nutrientes pela cultura da mamona (Ricinus communis L.) são restritas apenas aos macronutrientes (CANECChIO FILhO;FrEIrE, 1958;NAkAgAwA;NEPTUNE, 1971). Apesar dos micronutrientes serem absorvidos em pequenas quantidades, os mesmos, são fundamentais para o crescimento e o desenvolvimento das culturas (kIrkBy;röMhELD, 2007), sendo que a falta de qualquer um deles causa perdas significativas de produtividade.…”
unclassified